THE IMPACT OF AMERICAN STANDARD OF BEAUTY IN LOUISE’S LIFE IN THE FAT GIRL SHORT STORY BY ANDRE DUBUS - RIFKI, MINGGA YULIANA ENNUR (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Feminism, Standard of Beauty, Struggle Standard of beauty traps women to follow society ideals. The standard of beauty in America and most western societies has been an overall slim with light eyes and long straight hair. So they should fulfill what the standard beauty wants. Though obviously damaging, it is socially, even morally, acceptable to support our life standards of beauty. Women live in stressful times to show how their bodies look. Driven by guilt and shame, many women castigate themselves by doing strict diet and even doing a plastic surgery to achieve the standard of beauty without thinking about the dangers that will happen to their body. The standard of beauty impacts on Louise's life within a short story titled The Fat Girl by Andre Dubus. Therefore, the writer conducted this study to reveal the standard of beauty pressures and impacts experienced by the main woman character in the short story and also how the main character struggles to fight the standards of beauty in her environment. The writer looked at the impact of the standards of beauty and the efforts to struggle against standard of beauty by the main character through a feminist point of view. The result of this study reveals that there are some factors that influence Louise as the main character, such as her family, her friends and her husband who oppress her to fulfill the standard of beauty which exists in her environment. While the main character “Louise” in the story feels uncomfortable and feels pressured because she is a fat woman with eating habits. As the result, she can finally struggle herself against the American standard of beauty by keep eating and does not think about the standard of beauty. The writer suggests to the student of English Study Program, Languages and Literature Department of University of Brawijaya who intend to conduct a research on the same short story to use different perspectives such as psychological approach.